Physical activity and quality of life for 40 and 50 years old women - Lianys García-Álvarez (Universidad de Guantánamo, 2015)
The community development is the work with the different sectors of the society, inside them women. This research pursues as main objective the proposal of a methodology that allows the personnel of the Sport Complexes to improve the quality of life of 40 and 50 years old women. The methodology has a set of actions related to the therapeutic physical culture to respond to the limitations and problems characteristic of these ages, starting from a better methodological work with the professors in training. This investigation was approved by the commission of ethics of the Faculty of Medical Sciences of Guantánamo to assure the protection of the rights, security and well-being of the persons of the sample, the adaptation and methods to be used for the obtaining documentation of the informed consent of the participants.